Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 749: 149



Work Step by Step

$\frac{(x^{\frac{2}{3}}x^{-3})^{3}}{x^{-\frac{1}{2}}}$ =$\frac{(x^{\frac{2}{3}-3})^{3}}{x^{-\frac{1}{2}}}$ =$\frac{(x^{\frac{2-3(3)}{3}})^{3}}{x^{-\frac{1}{2}}}$ =$\frac{(x^{\frac{2-9}{3}})^{3}}{x^{-\frac{1}{2}}}$ =$\frac{(x^{\frac{-7}{3}})^{3}}{x^{-\frac{1}{2}}}$ =$\frac{(x^{-\frac{7}{3}\times3})}{x^{-\frac{1}{2}}}$ =$\frac{x^{-7}}{x^{-\frac{1}{2}}}$ =$\frac{1}{x^{-\frac{1}{2}+7}}$ =$\frac{1}{x^{\frac{-1+14}{2}}}$ =$\frac{1}{x^{\frac{13}{2}}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.